STUDY OF KINETICS OF BIOSORCION OF IONS LEAD IN PECTIN RETICUlATE FROM SHELLS OF CITRUS - García V., V. (2010)
Pectin is a mixture of polysaccharides containing galacturonic acid units, as main compound, into its structure and it is found by forming a part of the vegetables cell wall, such as citrus. Carboxylic groups in their anionic form are characterized for their binding capacity for cationic species such as Pb2+. Orange peels were used as a source of pectin, through acid hydrolysis (pH=1.4, temperature: 80°C, time: 60 min.). For decreasing the hydration and swelling capacity when pectin is found in aqueous solution medium, crosslinked by using formaldehyde was made. Maximum sorption capacity was obtained at pH between 4.5 and 5.5. The most of the cases Pseudo first arder mathematic kinetic model fit it better than Pseudo second arder to kinetic biosorption of lead in pectin for either difierent initial metal concentrations in solution or difierent amounts of biosorbent.